Factors and Principles of Improving the Hierarchical System of Sale of Insurance Products - Abdukhalilovna, Mavrulova Nilufar (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article discusses the issues of managing the sales system in an insurance company, and also analyzes the importance of a vertically integrated sales system for insurance products and its impact on efficiency. Also, when implementing the tariff policy, it is proposed to develop a tariff system for groups of risk factors, and the influence of an insurance company on financial stability is also expressed.